The Literary and Cultural Rhetoric of Victimhood - Naqvi, F. author. aut Link
XII, 264 p.
Keywords: In a series of paradigmatic readings of René Girard, Peter Sloterdijk, Michael Haneke, Anselm Kiefer, Michel Houellebecq, Elfriede Jelinek, Giorgio Agamben, Naqvi examines the current fascination with victimhood and the desire for victim status.